Digital marketing impact on consumer purchasing decisions: insights from the FMCG sector in Mthatha - Dumisana, Asemahle; Tlapana, Tshepo (Management and Entrepreneurship: Trends of Development, 2026)
This study investigated the impact of digital marketing on consumer purchasing decisions within the Fast-Moving Consumer Goods (FMCG) sector in Mthatha, South Africa. The research aimed to identify the most effective digital marketing channels, analyse key factors influencing consumer behaviour, and understand barriers to digital marketing adoption in a semi-urban context. A quantitative research design was employed using a descriptive survey method. The study targeted consumers aged 18 and above who regularly purchase FMCG products in Mthatha. A non-probability convenience sampling approach was adopted due to geographic constraints, resulting in a sample size of 100 respondents. Data was collected through structured questionnaires distributed both online and offline to ensure inclusivity. Descriptive and inferential statistical analyses were conducted using SPSS to examine relationships between digital marketing exposure and purchasing behaviour. The findings reveal that platforms such as Facebook, TikTok, and YouTube are the most influential in shaping consumer decisions, with promotions and user reviews identified as the most impactful content types. Influencer marketing also emerged as a key driver of trust and engagement. The study highlights infrastructural challenges, including limited internet access and high data costs, which hinder full adoption of digital marketing. Key recommendations include prioritizing social media platforms, leveraging influencer collaborations, and integrating promotional content and user reviews into marketing strategies. Furthermore, businesses should adopt hybrid marketing approaches and invest in digital literacy initiatives to enhance consumer engagement. JEL Classification: M31, M37, D12.